Two new species of the genus Ishigakia (Hymenoptera: Ichneumonidae, Acaenitinae) from Vietnam based on morphological and molecular evidence - Pham, Nhi Thi; Ito, Masato; Matsumoto, Rikio; van Achterberg, Kees (Zootaxa, 2018)
The genus Ishigakia is reported from Vietnam for the first time, and two new species (I. babeensis sp. nov. and I. duongi sp. nov.) are described from Northeast Vietnam using morphological and genetic data. These new species are also inserted in the key to world species of Ishigakia provided by Ito & Maeto (2016).